An integrated simulator for testing and validation of autonomous vehicle applications with physics-based rendering sensors - Muhammad Usman (2021)
Interest in Autonomous Vehicles (AVs) is gearing up tremendously in recent years with a focus on improving the safety and efficiency of the transportation system around the globe. Singapore being on the forefront of the deployment of AV related technologies for daily transportation needs, is playing a pivotal role in testing and validation of AVs in urban road traffic scenarios. Several industries and research organizations are collaborating in Singapore for bringing AVs on road. This work presents the development of an integrated realistic simulator that enables different sectors involving automotive, communication, infrastructure, instrumentation etc., to analyse their developed modules for deploying AVs. The integrated simulator is unique in its way that it includes physics-based customizable models for sensors, facility to test different climate conditions and usage of standardized open formats.In order to test the simulator performance, a simple use-case is analysed for path planning and control for autonomous valet parking. The aim of this platform is to be used for independent tests and analysing how AV will behave in the urban Singapore like scenarios. This will help in deploying AV services for various applications in different regions in Singapore.